2021
DOI: 10.1016/j.celrep.2021.109412
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous inflammation of BRCA1-deficient ovarian cancers drives both tumor-intrinsic immunoreactivity and immune resistance via STING

Abstract: SUMMARY In this study, we investigate mechanisms leading to inflammation and immunoreactivity in ovarian tumors with homologous recombination deficiency (HRD). BRCA1 loss is found to lead to transcriptional reprogramming in tumor cells and cell-intrinsic inflammation involving type I interferon (IFN) and stimulator of IFN genes (STING). BRCA1 -mutated ( BRCA1 mut ) tumors are thus T cell inflamed at baseline. Genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 76 publications
(105 reference statements)
3
64
0
Order By: Relevance
“…Moreover, tumors derived from a Brca1 -deficient cancer that progressed on treatment lose their ability to induce senescence and SASP upon cisplatin treatment, leading to resistance to cisplatin in combination with ICB. Interestingly, the increased propensity of Brca1 -deficient tumors to undergo senescence and/or activate the cGas/STING pathway appears to extend to other agents, as Brca1 -deficient models of breast and ovarian cancer treated with PARP inhibitors or, as shown here, taxol show similar behaviors ( 70 74 ). As such, senescence induction may underlie the improved response of HR-deficient tumors to genome destabilizing therapies in the clinic.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, tumors derived from a Brca1 -deficient cancer that progressed on treatment lose their ability to induce senescence and SASP upon cisplatin treatment, leading to resistance to cisplatin in combination with ICB. Interestingly, the increased propensity of Brca1 -deficient tumors to undergo senescence and/or activate the cGas/STING pathway appears to extend to other agents, as Brca1 -deficient models of breast and ovarian cancer treated with PARP inhibitors or, as shown here, taxol show similar behaviors ( 70 74 ). As such, senescence induction may underlie the improved response of HR-deficient tumors to genome destabilizing therapies in the clinic.…”
Section: Discussionmentioning
confidence: 64%
“…Different conclusions have been drawn about the role of CCL5 in tumors. Some studies accounted CCL5 for the promotion of tumor development by suppressing the immune response ( 19 ), whereas some studies regarded CCL5 as a tumor protective factor associated with high CD8+ T cell infiltration ( 20 , 21 ). In this study, we first evaluated the relationship between CCL5 and survival in patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that phosphorylation of H2AX at S139, known as γH2AX, triggered by active ATM kinase during double stranded DNA breaks can interact with HIF-1α to maintain its stability and nuclear accumulation, thereby facilitating HIF-1α/hypoxia signaling activation and predicting metastatic outcome (57). Homologous recombination deficiency such as BRCA1 loss can lead to upregulation of pro-angiogenic factors such as VEGF through transcriptional reprogramming in tumor cells via stimulator of interferon genes (STING) (58). Third, DDR defect and related DNA damages, on the other hand, may inhibit tumor metastatic potential by recruiting tumor infiltrating lymphocytes (TIL) to the microenvironment.…”
Section: Dna Damages and Tumor Microenvironment Remodelingmentioning
confidence: 99%